TRADITIONAL MARKET ARRANGEMENT STRATEGY, IN PERSPECTIVE OF SPATIAL POLICY IN INDONESIA - Aenun Istiqomah; Francisco Carballo; Arif Zainudin; Dika Pratama (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
In the midst of the development of modern markets, the existence of traditional markets must also be maintained. Traditional markets have various weaknesses that become basic characters that are difficult to change, ranging from spatial factors, slums, parking chaos, and other images that are not good compared to modern markets. Of course, if this weakness is not handled properly, the existence of the traditional market is threatened. There needs to be improvements and arrangements for traditional markets to build clean conditions and provide comfort for consumers and traders. The government's role is to maintain the existence of traditional markets which can be done with various alternative strategies. This study aims to determine the strategy of structuring traditional markets in Pangkah District and to determine the model of structuring the Pangkah market in Tegal Regency in an effort to maintain the existence of traditional markets. This research uses a mix method approach. Data collection techniques using observations, interviews, questionnaires with a Likert scale and literature studies. Data analysis was performed using the SWOT matrix QSPM method to determine alternative strategies. As well as being strengthened again in the depiction of maps using ArcGIS software which aims to see the condition of market activity through satellites. The results obtained showed that the Pangkah market activity was quite dense and obtained a strategy to develop the Pangkah market which aims to increase people's interest in shopping at the Pangkah market.